Narrative Structure of the Ne’ Baruakng Kulup Story Oral Literature of Dayak Kanayatn: A Study of Actantial A.J. Greimas - Sesilia Seli; Antonius Totok Priyadi; Sisilya Saman; Laurensius Salem (STKIP Singkawang, 2020)
This study is based on the importance of conducting an in-depth study of the characters of Ne’ Baruakng Kulup story of DayakKanayatn’s oral literature. This story narrates an attempt made by Baruakngto bring paddy into the earth which was full of obstacles so that he was named Ne’ BaruakngKulup. The aims of this study to describe the actantial schemes and functional structures in the Ne’BaruakngKulup story. The life dynamic of Baruakngis interesting to study more in-depth by using the study of narrative structure based on the thinking of A.J. Greimas. This qualitative study was focused on two important elements, namely: (1) the actantial scheme in the story of Ne’ BaruakngKulup; and (2) the functional structure in the story of Ne’ BaruakngKulup.The techniques of collecting data in this study were a documentary study and analyzed using structural approaches.The results of this study indicate that there are 14 actantial schemes and 14 functional structures. Four actant schemes and 4 perfect functional structures and 10 actantial schemes, and 10 imperfect functional structures. The main actantial scheme lies in the sixth actant scheme. There is a correlational relationship between the actant scheme and the functional structure. The character of Ne’ BaruakngKulup is a hero in the story analyzed.